2003
DOI: 10.3168/jds.s0022-0302(03)73763-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Silage and Grain from Glyphosate-Tolerant or Insect-Protected Corn Hybrids on Feed Intake, Ruminal Digestion, and Milk Production in Dairy Cattle,

Abstract: Lactating dairy cows were used to determine effects of feeding glyphosate-tolerant or insect-protected corn hybrids on feed intake, milk production, milk composition, and ruminal digestibility. Corn resistant to European corn borer (Ostrinia nubilalis) infestation (Bt-MON810), or its nontransgenic control (Bt-CON), were planted in alternating fields during two successive years. One-half of each strip was harvested for whole plant corn silage and the remainder was allowed to mature and harvested as grain. Effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 18 publications
9
42
0
2
Order By: Relevance
“…Lack of differences among treatments observed in all three experiments agrees with previous research evaluating glyphosate-tolerant corn and soybeans fed to dairy cattle (Donkin et al, 2003;Hammond et al, 1996), pigs (Cromwell et al, 2001;Stanisiewski et al, 2001;Gaines et al, 2001a), and poultry (Gaines et al, 2001b;Taylor et al, 2003). Donkin et al (2003) utilized silage and grain from Roundup Ready corn (event GA21) to examine effects of transgenic crops on feed intake, milk yield, and milk composition for sixteen lactating Holstein cows.…”
Section: Discussionsupporting
confidence: 79%
“…Lack of differences among treatments observed in all three experiments agrees with previous research evaluating glyphosate-tolerant corn and soybeans fed to dairy cattle (Donkin et al, 2003;Hammond et al, 1996), pigs (Cromwell et al, 2001;Stanisiewski et al, 2001;Gaines et al, 2001a), and poultry (Gaines et al, 2001b;Taylor et al, 2003). Donkin et al (2003) utilized silage and grain from Roundup Ready corn (event GA21) to examine effects of transgenic crops on feed intake, milk yield, and milk composition for sixteen lactating Holstein cows.…”
Section: Discussionsupporting
confidence: 79%
“…Consequently, the Cry toxin has become a genetic resource for developing insect-resistant, genetically modified (GM) plants including Bt11 [2]. Before the introduction of Bt11 corn, there were several studies to assess its safety based on livestock performance [1,4,5]. However, there is little knowledge available on the clinicobiochemical effects of feeding Bt11 to cattle.…”
mentioning
confidence: 99%
“…Effects of Bt corn on rumen functions that play an important role in digestion and absorption were also examined, and ruminal pH, acetate: propionate ratio, in situ digestion kinetics of NDF (neutral detergent fiber), efficiency of milk production, and daily body weight gain were unaffected by the transgenic corn 22 . Other feeding studies also demonstrated the equivalence of nutritional value of Bt corn and productivity of animal products from cattle fed Bt corn, compared with its nontransgenic control 18,23,58 . Additionally, the results of some compositional analyses and feeding studies of Bt cotton indicated that transgenic cotton is substantially equivalent to its non-transgenic control, similar to Bt corn 8,25 .…”
Section: Cattlementioning
confidence: 99%